Speaking Anxiety and Pronunciation Accuracy: A Correlational Study with Indonesian EFL Learners - Mamang, Siti Mariam; Rasuki, Muhlisin; Nurkamilah, Nurkamilah (Journal of English Language and Education, 2023)
Language anxiety constitutes a psychological phenomenon that commonly impacts second/foreign language (L2) learning and performance. Although language anxiety has been extensively studied in L2 research, there is a lack of research on the relationship between speaking anxiety and pronunciation accuracy. To address this gap, the current study investigates the potential influence of speaking anxiety on pronunciation accuracy in L2 speaking. Data were obtained from 30 Indonesian learners of English as a foreign language (EFL). These learners completed an L2 speaking task and a questionnaire. The speaking task assessed the learners’ ability to pronounce English words, while the questionnaire measured their levels of speaking anxiety. A correlational analysis of the data revealed a very weak correlation between speaking anxiety and pronunciation accuracy among the Indonesian EFL learners, and this correlation was not statistically significant: ρ(28) = 0.052, two-tailed p = 0.785. These findings suggest that the reported levels of speaking anxiety among the learners do not significantly impact their pronunciation accuracy in the given L2 English speaking task. This study contributes to the existing knowledge by shedding light on the underexplored relationship between L2 speaking anxiety and pronunciation accuracy.